2020
DOI: 10.13057/biodiv/d211257
|View full text |Cite
|
Sign up to set email alerts
|

Home range, movement and habitat selection of dholes (Cuon alpinus) in Khao Yai National Park, Thailand

Abstract: Abstract. Sukmasuang R, Suksavate W, Songsasen N, Khiowree N, Charaspet K, Pla-ard M, Chanachai Y, Thomas W, Srinopawan K. 2020. Home range, movement and habitat selection of dholes (Cuon alpinus) in Khao Yai National Park, Thailand. Biodiversitas 21: 5915-5926. This study aimed to examine the home range, movement and habitat selection of dholes (Cuon alpinus) in Khao Yai National Park from January 2017 to September 2019 with the objective of studying their movement, diel activity and habitat selection. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The influenced the probability of the appearance of dholes were environmental factors such as the distance from the village, elevation and wilderness areas (Namgyal and Thinley 2017). Sukmasuang et al 2020 reported that the grassland was also an important factor of the dhole.…”
Section: Introductionmentioning
confidence: 99%
“…The influenced the probability of the appearance of dholes were environmental factors such as the distance from the village, elevation and wilderness areas (Namgyal and Thinley 2017). Sukmasuang et al 2020 reported that the grassland was also an important factor of the dhole.…”
Section: Introductionmentioning
confidence: 99%